Des dimensions collectives comme dimensions génériques du travail humain et leurs déclinaisons dans des activités d'enseignement partenariales - Patricia Champy-Remoussenard (Université de Provence, 2014)
The research work analysis shows that collective dimensions are an almost universal feature of human labor that can therefore be considered as a generic and cross. They are variations in specific industries and different "professions". At a time when human labor changes significantly and fast, collective dimensions are also changing and part of a transformation of human relations professions, including those activities that educate, train, teach, accompany. Mobilizing the results of studies on collective dimensions in all work activities, can be renewed understanding of the activities of teachers, especially in their collective dimensions in that they contain hidden work and difficult to formalize. We first show that collective dimensions are generic dimensions of human labor, they are part of the visible evil character and its educational function. We will insist on the status they give to relationships with others, the relationship they have with the actual work, the construction process, transmission, assessment of skills. Finally, it is on this basis that the specificity of the collective dimensions of teachers' work will be discussed, particularly in the "partnership" devices that challenge the more traditional forms of teachers' work.